Infections associated with clozapine: a pharmacovigilance study using VigiBase® - Chrétien, Basile; Brazo, Perrine; Da Silva, Angélique; Sassier, Marion; Dolladille, Charles; Lelong-Boulouard, Véronique; Alexandre, Joachim; Fedrizzi, Sophie (Frontiers in Pharmacology, 2023)
Introduction: Clozapine is primarily reserved for treatment-resistant schizophrenia due to safety concerns associated with its use. Infections have also been reported with clozapine, which may lead to elevated serum levels of the drug. However, the existing literature on this topic is limited. Therefore, we conducted a study using VigiBase® to investigate the potential over-reporting of infections associated with clozapine, explore the presence of a dose-dependency, and investigate the underlying mechanism. Methods: Disproportionality analyses were performed in Vigibase to assess the association between clozapine and all types of infections, the association between clozapine-associated infections and neutropenia, the association between clozapine-associated infections and agranulocytosis, the dose-effect relationship between clozapine and infections, and the interaction between clozapine and the main strong CYP450 inhibitors using reports done until 11th of April 2023. Results: A statistically significant signal of infections was observed with clozapine, as indicated by an Information Component of 0.43 (95% CI: [0.41-0.45]). The most commonly reported infections were respiratory and gastro-intestinal in nature. Neutropenia showed weaker association with clozapine-associated reports of infections compared to other clozapine-associated reports (X2 (1, N = 204,073) = 454, p <0.005), while agranulocytosis demonstrated a stronger association with clozapine-associated reports of infections (X2 (1, N = 204,073) = 56, p <0.005). No evidence of dose-dependency was observed. Among the 17 tested CYP inhibitors, significant drug-drug interactions were found with clarithromycin, metronidazole, valproic acid, lansoprazole, omeprazole, amiodarone, and esomeprazole. Discussion: Our study revealed a significant safety signal between clozapine use and infections, predominantly respiratory and gastro-intestinal infections. Instead, the co-administration of clozapine with valproic acid or proton pump inhibitors may potentially contribute to an increased risk of infection. Further vigilance is warranted in clinical practice, and consideration of therapeutic drug monitoring of clozapine in cases involving concomitant use of these drugs or in the presence of infections may be beneficial.